Analisis Potensi Kecurangan Dalam Pengelolaan Keuangan Desa (Studi: Desa Kesongo, Kecamatan Tuntang, Kabupaten Semarang, Jawa Tengah) - Ismail Alfaruqi; Ika Kristianti (Universitas Kristen Maranatha, 2019)
Indonesia Corruption Watch (ICW) found 154 corruption cases during 2015-2017, most of them were corruption cases involving the village budget. The potential for fraud can be detected by cheating triangle theory, namely pressure, opportunity and rationalization. The purpose of this study is to identify potential fraud in village financial management. This study uses a qualitative approach and the type of data used is primary data obtained directly using interview techniques from the village financial management process conducted by the Village Financial Management Technical Officer (PTPKD) Kesongo Village, Tuntang District, Semarang Regency. The results of the study show that in the village financial management in Kesongo Village there is potential for fraud including: the necessity to do something; disciplinary behavior; feel that they are not detrimental to others and consider mistakes to be natural and often occur. This study concluded that in Kesongo Village there was potential for fraud in the process of village financial management. Keywords: Village Financial Management, Village Apparatus, Potential for Fraud, Control